The developmental pathways of senior international soccer players: A 13-year analysis of the career trajectories of the Swedish men`s senior international team - Sweeney, L.; Kalén, A.; Ivarsson, A.; Lundberg, T. R. (PLOS ONE, 2025)
This study explored the developmental pathways of all players (n = 313) who represented the Swedish men`s senior international team between 2011 and 2023 (n = 118) and/or the U21 international team between 2011-2022. We also examined at which respective level each player`s youth club was ranked (i.e., premier, second, or third division club, or international academy) and the age at which they were first present in that club environment. Of the 118 senior international players, 34% were selected at U15-U16, 33% were selected at U17-U18, and 33% were selected at U21 or the senior international level. Later selected (U21 and senior) players had a later senior international debut than early selected (U15-U16) players (-2.5 years, 95% CI [-4.0, -1.0 years]). Later selected players also made their senior club debut later than those selected at the U17-U18 (-1.3 years, 95% CI [-2.0, -0.5 years]) and U15-U16 (-1.9 years, 95% CI [-2.6, -1.1 years]) international level. While the majority (60%) of senior international team players entered a premier division club at some point during their junior years, players from lower clubs were overrepresented among the players who reached the senior international team without previous international team experience and made a later debut in the senior international team. We conclude that senior international players have different career trajectories and that this should be accommodated by providing structures that allow players to progress into, and out of, different development environments that best suit their individual needs as they progress to the senior level.